2021
DOI: 10.1177/10439862211038448
|View full text |Cite
|
Sign up to set email alerts
|

Racial Democracy and Black Victimization in Brazil

Abstract: The main objective of this study is to quantify racial victimization differential between Blacks and Whites in Brazil, focusing on homicides and physical assaults. Combining socioeconomic data from the Brazilian Household Survey with data from the Mortality Information System, we apply the Oaxaca–Blinder decomposition to isolate the racial discrimination component from the social indicators correlated with homicides and physical assaults. Findings indicate that only part of the victimization differential betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Returning to North America, racial discrimination is a pervasive problem, with over 50% of Black, Hispanic, and Asian people reporting racial discrimination (Lee et al, 2019). Similar data are available in, e.g., Brazil, where significant differences are found in racial victimization between Black and White Brazilians (Truzzi et al, 2022). Even if such documentation of racial discrimination can't readily be compared with Swedish conditions, racism clearly exists in both overt and covert forms in Sweden (Akrami et al, 2000;Hylland Eriksen, 2019;Quillian et al, 2019;Kristoffersson et al, 2021).…”
Section: Demographics and Discrimination Pertaining To Ethnicity And ...mentioning
confidence: 80%
“…Returning to North America, racial discrimination is a pervasive problem, with over 50% of Black, Hispanic, and Asian people reporting racial discrimination (Lee et al, 2019). Similar data are available in, e.g., Brazil, where significant differences are found in racial victimization between Black and White Brazilians (Truzzi et al, 2022). Even if such documentation of racial discrimination can't readily be compared with Swedish conditions, racism clearly exists in both overt and covert forms in Sweden (Akrami et al, 2000;Hylland Eriksen, 2019;Quillian et al, 2019;Kristoffersson et al, 2021).…”
Section: Demographics and Discrimination Pertaining To Ethnicity And ...mentioning
confidence: 80%
“…Contemporary research has revealed that racial disparity does exist within institutions in Brazil, such as the economy (Arcand & D’hombres, 2004), education (Botelho et al, 2015; Marteleto & Dondero, 2016), and health outcomes (Nyarko et al, 2013; Pavao et al, 2012). Statistics also demonstrate the presence of racial disparities in criminal victimization (Murray et al, 2013; Truzzi et al, 2021), although existing studies have presented mixed results regarding how race influences the decision-making for homicide cases brought to the criminal justice system (Adorno, 1995; Cano et al, 2010; Costa Ribeiro, 1995; Fausto, 1984; Ribeiro, 2010; Ribeiro & Diniz, 2020). Adding to the above empirical findings, the current study finds no direct effects of race on jurors’ decisions about conviction but finds racial disparity in judicial decisions of sentence length.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of homicide in Brazil has a significant impact on the population, as research has found that nearly 50 million Brazilians over the age of 16 (about one-third of the population) have lost friends or relatives to murder (Brazilian Forum of Public Safety, 2019). Racial disparities in homicide are also particularly pronounced, with homicide victimization rates for Black persons (37.8 homicides per 100,000) exceeding the rate of non-Blacks (13.9 homicides per 100,000 in 2018 [Truzzi et al, 2021; see also Murray et al, 2013]).…”
Section: Race Homicide Sentencing and The Brazilian Contextmentioning
confidence: 99%
See 2 more Smart Citations